Regenerative Medicine - Steinhoff, Gustav (Springer, 2011)
Regenerative Medicine is a fastly emerging interdisciplinary field of research and clinical therapies on the repair, replacement or regeneration of cells, tissues or organs in congenital or acquired disease. This new field of research and clinical development focussing on stem cell science and regenerative biology is just starting to be the most fascinating and controversial medical development at the dawn of the 21st century. Viewing the great expectations to restructure and regenerate tissue, organs or organisms the current attempts of scientist and physicians are still in an early phase of development. This new textbook on ?Regenerative Medicine ? from protocol to patient? is aiming to explain the scientific knowledge and emerging technology as well as the clinical application in different organ systems and diseases. The international leading experts from four continents describe the latest scientific and clinical knowledge of the field of ?Regenerative Medicine?. The process of translating science of laboratory protocols into therapies is explained in sections on basic science, clinical translation, regulatory, ethical and industrial issues. The textbook is aiming to give the student, the researcher, the health care professional, the physician, and the patient a complete survey on the current scientific basis, therapeutical protocols, clinical translation and practised therapies in Regenerative Medicine.